MINERAL COMPOSITION OF Fe-POOR FERRUGINOUS AND CARBONACEOUS SHALES FROM THE ALEXANDRINSKOE AND SAF′YANOVSKOE DEPOSITS (THE URALS) - N.S. Arkhireeva; V.A. Kotlyarov (Минералогия)
Ferruginous and carbonaceous shales of the Alexandrinskoe and Saf′yanovskoe massive sulfide deposits are composed of pseudomorphic chlorite, quartz and hydromica after hyaloclasts and contain quartz and plagioclase clasts, as well as zircon, apatite, rutile, siderite, barite, pyrite, marcasite, chalcopyrite, pyrrhotite, sphalerite and galena. Ferruginous shales also host hematite, maghemite, magnetite, epidote, dolomite, bornite, stutzite, rucklidgeite, altaite and pseudomorphic quartz after radiolarians. Carbonaceous shales contain organic matter, graphite, xenotime, titanite, tennantite, freibergite, acanthite, arsenopyrite and Sr alumophosphate similar to goedkenite. Pseudomorphs of apatite and quartz after foraminiferas are typical of carbonaceous shales.